Improvement of eggshell quality by dietary N-carbamylglutamate supplementation in laying chickens - Ma, Yanfen (Poult Sci, 2020)
Egg quality defects seriously reduce the quality grade and increase egg breakage in egg marketing activities. In this study, the effect of N-carbamylglutamate (NCG) on eggshell quality was investigated by evaluating calcium absorption and calcification in laying hens. A total of 30 newly hatched female Hy-Line chicks were randomly assigned to the control group (basal diet) and treatment group (basal diet supplemented with 1% NCG). At 25 wk, eggs from each group were obtained to assess egg quality parameters. Blood samples were collected for analysis of mineral, hormone, and amino acids levels at 16 h after laying egg. Uterine tissues were removed and fixed in 4% neutral paraformaldehyde solution or kept in liquid nitrogen for mineral determination, quantitative PCR, and Western blot. Results showed that the egg quality (eggshell thickness, strength and percentage, egg specific gravity, and eggshell effective thickness) was significantly increased while effective thickness of mastoid layer, width of mastoid gap, and mammillary knobs were significantly decreased by dietary NCG supplementation (P < 0.05). The levels of minerals (Ca, P, Fe, Mg, Na, K) in eggshell, plasma, and uterus were remarkably elevated (P < 0.05). Meanwhile, the concentrations of calcium metabolism–related hormones (17β-estradiol, parathyroid hormone, and calcitonin) were increased in the NCG group (P < 0.05). Moreover, expression of calbindin 1, carbonic anhydrase 2, ovalbumin, ovotransferrin, ovocleidin-17, ovocleidin-116, and clusterin mRNAs, as well as calbindin 1 and ATP2A1 proteins in uterus, duodenum, and kidney, was all upregulated in hens fed with NCG (P < 0.05). In addition, the number of blood vessels in the uterus, height of uterine mucosal folds, villus length in endometrium, and areas of uterine mucosal folds were significantly increased in the NCG group (P < 0.05). In conclusion, dietary 1% NCG supplementation during 0 to 25 wk can improve eggshell quality through changes in endometrial morphology, expression of calcium metabolism–related genes, and secretion of related hormones to promote eggshell formation in the laying hens.